STUDI PEMANFAATAN ABU TERBANG LIMBAH HASIL PEMBAKARAN CAMPURAN CANGKANG DAN SERABUT KELAPA SAWIT SEBAGAI SUBSTITUSI SEMEN PADA PEMBUATAN BETON NORMAL DI LAHAN BASAH - Rahman, Fauzi; Hidayat, Gawit; Bertiani, Novita (INFO-TEKNIK, 2020)
According to the Badan Pusat Statistik data in 2018, the total area of oil palm plantations in Indonesia currently reaches around 12.3 million hectares. Solid waste is the most waste, which is around 35-40% of the total Fresh Fruit Bunches (FFB) which is processed in the form of empty fruit bunches, fiber, fruit shells, and burnt ash. PT. Hasnur Citra Terpadu in Rantau, Tapin Regency, South Kalimantan is one of the Palm Oil Mill which in the combustion process of a boiler engine using oil palm shells and fibers is burned simultaneously. The result of the combustion process produces waste in the form of boiler crust ash which is fine textured (fly ash) and coarse textured (bottom ash). This study uses fly ash as a cement substitution for concrete mixtures. The making of mortar specimens was varied with fly ash with a percentage of 0%, 10%, 15%, 20% and 25% which will be tested for compressive strength at the age of 3 days, 7 days, 14 days, 21 days, and 28 days. Then the making of concrete specimens is planned with a quality of 25 MPa and the concrete compressive strength is tested at the age of 3 days, 7 days, 14 days, 28 days and 56 days and the split tensile strength test of the concrete at 28 days. Based on the results of the mortar compressive strength analysis, the optimum mixture of fly ash is 10% which is used for making concrete. The average compressive strength of normal concrete at 28 days is 26.33 MPa and the compressive strength of concrete with 10% fly ash (optimum concrete) is 26.14 MPa exceeding the design compressive strength of 25 MPa. Based on the results of the split tensile strength test of concrete at the age of 28 days, it was obtained 3,914 MPa for normal concrete and 3,466 MPa for optimum concrete.